قاعدة عدم التحديد في الأحكام الشرعية عند علماء المالكية - بن عيسى عبد المليك; الحدي نو ا رلدين; د/بوفاتح الطيب (جامعة عمار ثليجي الاغواط, 2023)
عنوان البحث : د ا رسة قاعدة عدم التحديد في الأحكام الشرعية عند فقهاء المالكية د ا رسة فقهية - مقاصدية نماذج من باب العبادات - وقد احتوى البحث على مفاهيم عامّ ة حول القاعدة بتع ريفها بمفرداتها و جملتها وذكر مدلولها في الاصطلاح مع بيان ألفاظ هذه القاعدة عند م ن ذكرها من العلماء اولألفاظ ذات الصلة وأدلة عدم التحديد لبعض الأحكام الشرعية التي تدل على أصل القاعدة. ثم ذكرنا شيئًا من مقاصد القاعدة؛ وأسباب عدم التحديد وعلاقة القاعدة بمباحث من علم أصول الفقه ورفعنا الاشتباه عن علاقة هذه القاعدة بخاصية الضبط التحديد في الفقه. وفي الجانب التطبيقي اخترنا نماذج من أبواب العبادات في كل باب ثلاثة مسائل فقهية، بدأت بتمهيد للمسألة وذكر محل الاتفاق وتحرير الن ا زع وتوثيق الفرع الفقهي الدّ ال على عدم التحديد وشرح معناه والاستدلال له والتعليل لدلالته، ثم عقد د ا رسة مقاصدية لعدم التحديد في هذه المسألة. 722 Research Summary: Title of the research: A Comprehensive Study of the Principle of Indeterminacy in Legal Rulings According to the Maliki Jurists - A Jurisprudential and Maqasid-based Study - Examples from the Chapter of Worship. The research included general concepts about the principle, its definition, terms, and its significance in terminology. It also mentioned the terminology used by scholars to refer to this principle and related terms, as well as evidence of indeterminacy in some legal rulings indicating the origin of the principle. We then discussed some of the purposes and objectives of the principle, the reasons for indeterminacy, and the relationship between the principle and the discussions in the field of Usul al-Fiqh (Principles of Islamic Jurisprudence). We clarified the misconception regarding the association of this principle with the specific aspect of definitive rulings in fiqh. In the applied aspect, we selected examples from the chapters of worship, where each chapter included three fiqh issues. We began with an introduction to the issue, mentioned the points of agreement and areas of disagreement, and highlighted the specific fiqh branch indicating indeterminacy. We explained the meaning of the branch, provided evidence for it, and justified its implications. Finally, we conducted a maqasid-based study of indeterminacy in each of these issues.